2012
DOI: 10.1111/j.1582-4934.2011.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human ZNF300 gene enhances growth and metastasis of cancer cells through activating NF‐kB pathway

Abstract: Zinc finger proteins (ZNF) play important roles in various physiological processes. Here we report that ZNF300, a novel zinc finger protein, identified specifically in humans, promotes tumour development by modulating the NF-κB pathway. Inflammatory factors were found to induce ZNF300 expression in HeLa cell line, and ZNF300 expression further enhanced NF-κB signalling by activating TRAF2 and physically interacting with IKKβ. Furthermore, ZNF300 overexpression increased ERK1/2 phosphorylation and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Nonetheless, using both knockdown and overexpression strategies, we found that ZNF367 inhibited cancer growth and invasion, which suggests that the elevated levels in cancer samples are counter-regulatory and inhibit cancer progression. This finding is consistent with recent studies showing the diverse functions of other ZNF proteins in cancer biology and in mediating resistance to chemotherapy [9], [10], [13]-[15]. Moreover, we demonstrate that the increased levels of ZNF367 are likely a result of a loss in expression of miR-195.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, using both knockdown and overexpression strategies, we found that ZNF367 inhibited cancer growth and invasion, which suggests that the elevated levels in cancer samples are counter-regulatory and inhibit cancer progression. This finding is consistent with recent studies showing the diverse functions of other ZNF proteins in cancer biology and in mediating resistance to chemotherapy [9], [10], [13]-[15]. Moreover, we demonstrate that the increased levels of ZNF367 are likely a result of a loss in expression of miR-195.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies suggest that the NF‐κB pathway is involved in regulation of directional migration . The NF‐κB pathway widely participates in gene expression and regulation of chemokines, cytokines and adhesion molecules . The IκB kinase (IKK) complex consists of two catalytic subunits (IKK‐α and IKK‐β) and a regulatory subunit (IKK‐γ/NEMO).…”
Section: Discussionmentioning
confidence: 99%
“…The ZNF300 SNP rs4958427 was associated with immediate reactions to BL in the Spanish population but not in the Italian population. This gene encodes a transcription factor involved in the NF-κB signaling pathway and could have an effect on HLA-DRA expression [25]. In addition, this gene, together with NOD1 and NOD2, has been strongly associated with inflammation in Crohn disease [26].…”
Section: Immediate Reactions To Bl Antibioticsmentioning
confidence: 99%